Efficient form-finding algorithm for freeform grid structures based on inverse hanging method. (1st April 2022) - Zhao, Zhongwei; Yu, Duo; Zhang, Tongrui; Zhang, Ni; Liu, Haiqing; Liang, Bing; Xian, Lina
Abstract: Grid structures and branching columns have been widely adopted due to their high structural efficiency and novel appearance. High structural efficiency must be achieved through a strict form-finding analysis. Existing algorithms are mainly applicable for grid structures or branching columns only. However, the form-finding of upper grid structures and the lower branching columns are mutually affected. A form-finding algorithm is needed for grid structures supported by branching columns. In the present work, an efficient form-finding algorithm suitable for grid structures is initially proposed, and the feasibility of this algorithm is verified through three examples. Then, the form-finding algorithm for grid structures is integrated with the form-finding algorithm of branching columns. Results indicated that the proposed algorithm can be used for form-finding analysis of various grid structures supported by branching columns. This work was conducted using a general finite element analysis program and can be easily mastered by engineering designers while avoiding tedious programming. Highlights: An efficient form-finding algorithm suitable for grid structures is firstly proposed. The integrated form-finding algorithm for grid structures and branching columns is proposed. The mutually effect between the upper structures and the lower columns can be automatically considered.